Weight management telehealth intervention for overweight and obese rural cardiac rehabilitation participants: A randomised trial. Issue 9 (12th February 2019) - Barnason, Susan; Zimmerman, Lani; Schulz, Paula; Pullen, Carol; Schuelke, Sue
Abstract: Aims and Objectives: To determine whether a weight management intervention (WMI) plus cardiac rehabilitation (CR) compared to CR alone improves outcomes for overweight and obese cardiac revascularisation patients. Background: Despite participating in cardiac rehabilitation (CR), few cardiac patients lose enough weight to achieve clinically significant cardiovascular disease risk reduction. Design: A randomised controlled design was used with measurements at baseline, 4 and 6 months, guided by the CONSORT checklist, see Supporting Information FileS1 . Adults who had undergone either coronary artery bypass surgery (CABS) or percutaneous coronary intervention (PCI) and participated in a rural CR programmes were recruited. Subjects were randomised to a 12‐week telehealth WMI or control group. The primary outcome was weight loss. Secondary outcomes included physical activity, patient activation, perceived self‐efficacy and use of weight management behaviours. Results: A total of 43 subjects participated, with a mean age of 63 (±9.3) years. The WMI group had significantly more weight loss averaged across the 4 and 6 months of 13.8 (±2.8) pounds compared to the control group [mean = 7.8 (±2.2) pounds]. There were no significant differences in physical activity (activity counts or daily minutes in moderate or more intense activity). The WMI group had significantly higher levels of patient activation. They also had significantly higher total scores on the Diet and Exercise Self‐Management survey, and subscales that included self‐efficacy for specific eating habits and managing diet behaviour. Conclusions: Findings demonstrated the usefulness and feasibility of using telehealth delivery of the WMI for cardiac rehabilitation participants in rural communities to improve weight management outcomes. Relevance to Practice: Study findings underscore the opportunity to further improve weight loss of overweight and obese cardiac participants using a weight management intervention to augment CR participation.